O privire de ansamblu asupra câtorva instituţii culturale în România, între Primul Război Mondial şi perioada actuală - Simu, Mona (Calitatea Vieții, 2019)
The article presents, in the first part, an analysis of statistical data on several cultural institutions (theatres, cinema, libraries, books and museums) in Romania, between the years following the first world war and nowadays times. Each of the three main periods between 1938 and 2016 is studied separately: interwar period; communism; the period of transition, after December 1989. The results are showing a general upword development trend, with some discrepancies between some of the institutions. As for public libraries and cinemas, communism seems to be the most prolific period, for books and museums present times are the most “productive”. Every institutions has its own up and down, which can be seen from the five graphics embeded in the text. In the second part, a short view on the cultural life in Romania between the two World Wars is ellaborated, looking upon cultural personalities and facts. The article intends to offer a wide perspective image,yet not exhaustive, upon the cultural sphere in Romania, in almost one hundred years of social development.